Effect of joint thickness on seismic response across a rock fracture filled with dry granular materials. Issue 3 (9th July 2018) - Li, X. F.; Li, H. B.; Li, J. C.; Zhao, J.
Abstract : This study aims to investigate the influence of joint thickness on seismic response across a filled fracture with strong nonlinear deformability. In order to simulate seismic attenuation of thicker joints subject to high amplitude stress waves, the split Hopkinson pressure bar is utilized to generate normally incident P wave and the dry quartz sand is used to simulate the filled joints. Three joint thicknesses, i.e. 5, 10 and 15mm, are studied under identical incident waves. The stress-strain response of the filling materials is described by Barton-Bandis model having different loading/unloading behaviours. The initial stiffness and the maximum allowable closure of the joints changing with the joint thickness are studied. The thicker joints result in lower initial stiffness and cause lower seismic wave transmission across the fracture. The high amplitude stress strengthens the nonlinearity of the filling materials and increases the stiffness. Besides, the seismic attenuation factor Q, derived from the energy dissipation, is lower than that computed by the transmission coefficient due to the frequency filtering.